Reduction in cytoplasmic lipid content in bovine embryos cultured in vitro with linoleic acid in semi-defined medium is correlated with increases in cryotolerance - Accorsi, Mônica F. [UNESP]; Leão, Beatriz Caetano da Silva [UNESP]; Rocha-Frigoni, Nathália Alves de Souza [UNESP]; Perri, Silvia Helena Venturoli [UNESP]; Mingoti, Gisele Zoccal [UNESP] (Cambridge University Press, 2015)
We examined whether culturing embryos with linoleic acid (LA) in semi-defined medium reduces lipid accumulation and improves cryosurvival after vitrification. Embryos were cultured with LA (100 μM) and a semi-defined medium was used during in vitro culture (IVC), in which the fetal calf serum was substituted by bovine serum albumin (BSA). There was a reduction (P < 0.05) in the embryonic development rate (Control: 25.8% versus LA: 18.5%), but the proposed system was effective in promoting the decrease (P = 0.0130) in the intracellular lipid content (Control: 27.3 ± 0.7 versus LA: 24.6 ± 0.7 arbitrary fluorescence units of embryos stained with the fluorescent dye Nile Red), consequently increasing (P = 0.0490) the embryo survival after 24h of culture post-warming (Control: 50.0% versus LA: 71.7%). The results question the criteria used to evaluate the efficiency of an in vitro production system specifically with relation to the maximum number of blastocysts produced and suggest that might be more appropriate to improve the desired characteristics of embryos generated in accordance with the specific purpose of in vitro embryo production, commercial or scientific. In conclusion, supplying LA to serum-free culture medium was found to adversely affect the rates of embryo development to the blastocyst stage, but significantly reduced embryo lipid accumulation and improved cryopreservation survival.
Keywords: In vitro production; Bovine embryo; Linoleic acid; Lipid; Vitrification